Monitoring and assessment activities and indications of empathic behavior of the examined teachers during physical education lessons - Radoslaw Muszkieta; Piotr Oleśniewicz; Mirosława Cieślicka; Marek Napierała (Nicolaus Copernicus University in Toruń, Poland - University Sports Center, 2015)
The material of the studies was the physical education teachers of randomly chosen Poznań (Poland) schools: primary, grammar, and secondary schools. The studies involved 584 physical education teachers. The studies were conducted in the school year of 1999-2000. For the studies, an observation method was applied consisting in lesson observations during physical education lessons carried out by physical education teachers. The results of the studies form characteristic upward or downward tendencies. The higher the educational stage the higher the percentage value for the teachers who: a) assess attitudes and behavior of the students; b) monitor and assess knowledge of the students in the field of physical culture; c) assess with grades or points motor and organizational skills; d) assess verbally tasks' achievement; e) apply and introduce self-monitoring and self-assessment of knowledge, skills, attitudes, and physical fitness of the students. The downward tendencies were observed exclusively for monitoring attitudes and behavior of the students (i.e. having sports outfit, activity, involvement, attendance, etc.). The examined women were characterized by better and more positive empathic behavior. For all parameters, the women appeared to be better.